Recognition of nitrogen-responsive upstream activation sequences of Saccharomyces cerevisiae by the product of the GLN3 gene. - Blinder, D (1995)
We describe the purification of the product of the GLN3 gene of Saccharomyces cerevisiae and the demonstration that the purified product, Gln3p, binds specifically to the DNA sequences GATAAG and GATTAG, previously identified as nitrogen-responsive upstream activation sequences (UASN). When Gln3p is overproduced, it is released from the cells in a highly aggregated form incapable of specific binding to UASN. We used Gln3p tagged with six histidine codons at the 5' terminus and equipped with a galactose-inducible promoter to overproduce histidine-tagged Gln3p. The material was denatured, adsorbed to an Ni-nitrilotriacetic acid (NTA)-agarose column, eluted with imidazole, and after renaturation further purified on a gel filtration column. We then demonstrated the specific binding of the more than 90% pure Gln3p to the UASN by gel shift and footprinting methods.